1993
DOI: 10.1159/000116926
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cerebral Blood Flow in Multiple Sclerosis Measured by Single Photon Emission Tomography with Technetium-99m Hexamethyl-propyleneamine Oxime

Abstract: The regional cerebral blood flow (rCBF) in 19 patients with multiple sclerosis (MS), 10 with a relapsing remitting course and 9 with a progressive course, was examined by single photon emission computed tomography (SPECT) using technetium-99m hexamethylpropyleneamine oxime ([99mTc]-d,/-HM-PAO) as flow tracer. Nine age-matched volunteers served as controls. Low rCBF in the frontal grey matter correlated with neurological disability (p < 0.01), low frontal grey and white matter perfusion correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 10 publications
3
45
0
1
Order By: Relevance
“…This is in line with the findings of previous studies using PET and singlephoton emission computed tomography (Blinkenberg et al, 2000;Brooks et al, 1984;Lycke et al, 1993;Paulesu et al, 1996;Pozzilli et al, 1991;Roelcke et al, 1997), which have demonstrated a generalized coupled reduction in both cerebral oxygen utilization and blood flow in patients with established MS. Hypoperfusion was reported in both WM and GM and correlated with cognitive impairment rather than with locomotor disability, thus reiterating that the EDSS is heavily weighted toward locomotor disability and that the cerebral functional system is of limited sensitivity. Most PET and single-photon emission computed tomography studies, however, investigated only patients affected by RR-MS and, with very few exceptions (Paulesu et al, 1996;Pozzilli et al, 1991), cognition was assessed using the mini mental status scale or the cerebral functional system of the EDSS.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with the findings of previous studies using PET and singlephoton emission computed tomography (Blinkenberg et al, 2000;Brooks et al, 1984;Lycke et al, 1993;Paulesu et al, 1996;Pozzilli et al, 1991;Roelcke et al, 1997), which have demonstrated a generalized coupled reduction in both cerebral oxygen utilization and blood flow in patients with established MS. Hypoperfusion was reported in both WM and GM and correlated with cognitive impairment rather than with locomotor disability, thus reiterating that the EDSS is heavily weighted toward locomotor disability and that the cerebral functional system is of limited sensitivity. Most PET and single-photon emission computed tomography studies, however, investigated only patients affected by RR-MS and, with very few exceptions (Paulesu et al, 1996;Pozzilli et al, 1991), cognition was assessed using the mini mental status scale or the cerebral functional system of the EDSS.…”
Section: Discussionsupporting
confidence: 92%
“…1 R 27 Similarly, early SPECT work suggested that hypoperfusion of frontal regions correlated well with neurological disability and distinguished relapsing-remitting patients from progressive patients. 19 Early PET work by Brooks et ae 6 demonstrated a reduction in cerebral oxygen utilization and blood flow in both gray and white matter, which correlated well with cognitive impairment. A decrease in blood flow in the superior temporal cortex, as assessed by SPECT, correlated well with verbal fluency and memory deficits in MS. 1~ These studies suggest that gray matter abnormalities may play an important role in defining the dynamic pathophysiological expression of MS .…”
Section: Discussionmentioning
confidence: 97%
“…Early measurements of global perfusion in multiple sclerosis using radioactive 133 Xe [31], positron emission tomography (PET) [32], or single photon emission computed tomography (SPECT) techniques [33] suffered from a very low spatial resolution. Findings of a generally lower perfusion in MS patients compared to healthy individuals were contradicted by the demonstration of increased perfusion during the time of acute inflammation in an animal model of MS [34].…”
Section: Cerebral Perfusion Changes Precede Blood-brain Barrier Breakmentioning
confidence: 99%